Love & Eroticism. - Featherstone, Mike (Published in association with Theory, Culture & Society., 1999)
This major collection explores the nature of love and eroticism, examining the ways in which erotic bodily pleasures have become central to contemporary consumer culture. Drawing on the work of feminists, sociologists and cultural theorists, it contains wide-ranging and accessible contributions to contemporary debates on sexuality, love and eroticism.